The Mediating Role of Open Innovation in the Relationship Between Strategic Agility and Hospitality Performance: Evidence from the Hospitality Sector in Indonesia - Anugerah Dachi; Karsimin Karsimin; Pri Pantjaningsih; Elly Siti Nurliyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Hotel performance is the main factor to support the sustainability of the hotel business. Therefore, companies need to continue to maintain hotel performance to survive. The research aims to examine the effect of strategic agility, open innovation, and hospitality performance in the hotel industry in Bogor, West Java, Indonesia. Open innovation is the intervening variable that will be tested. The quantitative research method approach used was used in this study. Samples were obtained from as many as 97 respondents. This study's respondents were hotel industry employees, namely Reddorz and Oyo in Indonesia. Hypothesis testing was carried out using the structural equation modeling method. Research shows that there is an influence between strategic agility on open innovation, strategic agility and open innovation have an effect on hospitality performance. The results of the study also show that open innovation mediates the effect of strategic agility on hospitality performance.